2006
DOI: 10.3748/wjg.v12.i38.6198
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53, Bax and Bcl-2 proteins in hepatocytes in non-alcoholic fatty liver disease

Abstract: Apoptosis is one of the most important mechanisms leading to hepatocyte elimination in NAFLD. The intensification of inflammation in NAFLD induces proapoptotic protein p53 with the inhibition of antiapoptotic Bcl-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 21 publications
9
72
0
Order By: Relevance
“…A recent report showed that p53 activation correlated with susceptibility to ethanol-induced liver damage, a pathologic condition that is thought to mechanistically resemble NASH [20]. In addition, hepatic p53 expression and hepatocyte apoptosis increase in patients with NASH and a mouse model of NASH [7,8]. These results suggest that p53 plays a role in the pathophysiology of NASH, although the precise contributions have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report showed that p53 activation correlated with susceptibility to ethanol-induced liver damage, a pathologic condition that is thought to mechanistically resemble NASH [20]. In addition, hepatic p53 expression and hepatocyte apoptosis increase in patients with NASH and a mouse model of NASH [7,8]. These results suggest that p53 plays a role in the pathophysiology of NASH, although the precise contributions have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species (ROS), which are thought to make major contributions to aging, stimulate p53 stabilization and subsequent induction of apoptosis via a feed-forward regulatory loop [6]. Hepatic p53 expression is elevated in patients with NASH [7]. A recent report has also shown that hepatic p53 expression and hepatocyte apoptosis significantly increase in a mouse model of NASH [8].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism of organ fibrosis has not yet been comprehensively clarified due to its complexity, and thus far, whether p53 is directly involved in its pathophysiology has not been addressed. Recently, p53 has been shown to accumulate in hepatocytes of several fibrotic liver diseases, such as non-alcoholic steatohepatitis (NASH) (8,9), viral hepatitis (10,11), and primary biliary cirrhosis (PBC) (12). However, the precise role of p53 in liver fibrosis is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Other work has observed that the inflammation in human liver that occurs with NAFLD and NASH is paralleled with increases in p53 [76]. This has also been supported by p53 activation of mitochondrial pathways of apoptosis in an animal model of NASH [77].…”
Section: Mir-34amentioning
confidence: 78%